2021
DOI: 10.21037/apm-21-1014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the value of N-terminal pro-B-type natriuretic peptide (NT-proBNP) and other parameters related to right heart function in detecting acute radiation-induced right heart injury

Abstract: Background:The aim of the present study was to investigate the value of parameters related to right heart function combined with N-terminal pro-B-type natriuretic peptide (NT-proBNP) in acute radiation-induced right heart injury.Methods: Seventy patients who received chest radiotherapy (RT) in the RT department of our hospital between September 2015 and March 2019 were included in the study. Results: Of the included 70 patients, 19, 32, 4, and 15 had thoracic esophageal cancer, central lung cancer, thymoma, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Li et al. ( 27 ) observed an initial decrease in right heart function following radiotherapy for thoracic tumors. Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. ( 27 ) observed an initial decrease in right heart function following radiotherapy for thoracic tumors. Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial lack of data about the effect of radiotherapy on RV remodeling in patients with other types of cancers. A study that included 70 patients with esophageal cancer, central lung cancer, thymoma and left breast cancer showed that TAPSE and the Tei index were sensitive indicators for the early detection of right heart injury after RT for thoracic tumors [5]. Nevertheless, the 3D RV ejection fraction revealed no significant change in the early stage of right heart damage after radiotherapy.…”
Section: Thoracic Cancers (Lung and Esophagus)mentioning
confidence: 98%
“…Nevertheless, various parts of the heart are radiated and affected differently, which mainly depends on tumor localization [1]. The majority of studies have investigated the effect of radiotherapy on the left ventricle (LV) [2,3], whereas the effect on the right ventricle (RV) has been studied significantly less [4][5][6]. Novel reports are more focused on subclinical LV changes that correspond with the deterioration of LV multidirectional strain [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that 6 weeks after RT exposure, there was a small reduction in the global right ventricle strain and in the apical and the mid segments and that at 12 months there was a statistically significant GLS right-ventricle reduction [ 84 ]. Li J et al showed that the Tei index of the right ventricle and tricuspid annular displacement can be used as markers of right heart injury after RT for thoracic tumors [ 85 ].…”
Section: Cardiac Imaging Follow-up In Patients Receiving Rt For Breas...mentioning
confidence: 99%
“…In right-sided cancer, strain and tissue Doppler seem to decrease in the basal anterior left ventricle myocardium, but global heart function remains unchanged, while for left sided-breast cancer, changes in the apical territory, as well as a decline in GLS have been found. Those changes appear to be mirrored in some cases by ECG changes in the same territories and by slight increases in hs-cTnI and NTproBNP [ 85 ].…”
Section: Cardiac Imaging Follow-up In Patients Receiving Rt For Breas...mentioning
confidence: 99%